Postrefractive infectious keratitis: prevention, diagnosis, management, and prognosis. Issue 4 (July 2021) - Viriya, Elizabeth; Mah, Francis
Abstract : Purpose of review: Improve outcomes from an elective procedure by preventing a rare but sight-threatening complication. Recent findings: Advancement in anti-infective prophylaxis, and therefore shift in the causative organism permits better diagnostic and empiric management. Summary: Infectious keratitis presents in different patterns depending on the refractive procedure. Atypical causative organisms may respond poorly to empiric therapy and impair vision. Therefore, microbial identification is of utmost importance and therapy is adjusted accordingly.